Case-Based Learning Innovation Strategies in Financial Management of Service Companies: Collaboration Between Universities and Industry to Improve Student Competence - Wufron, Wufron; Muminin, Riyadh Sabilul; Febriani, Arini; Toha, Mohammad (Fakultas Ekonomi Universitas Garut, 2024)
This study aims to analyze the application of the case study method in improving students' critical thinking skills and enthusiasm in the Financial Management course in the Management Study Program, Faculty of Economics, Universitas Garut. The case study method is used in three learning cycles to evaluate students' ability to identify problems, analyze problems, seek information, draw conclusions, and present the results of their analysis in front of the class. The results of the study show that the application of the case study method is able to improve students' critical thinking skills, especially in topics such as cash flow management, financial statement analysis, investment decisions, and financial planning. In addition, the level of student enthusiasm has also increased significantly, which is reflected in their response, interest, and active participation during lectures. The role of lecturers as motivators, facilitators, and evaluators has proven to be effective in creating an interactive and conducive learning atmosphere. These findings make an important contribution to the development of more relevant and participatory learning methods in the field of financial management.